Wiki government : how technology can make government better, democracy stronger, and citizens more powerful - Noveck, Beth Simone (Brookings Institution Press, 2009)
"In explaining how to enhance political institutions with the power of networks, examines the Peer-to-Patent project. Discusses its design challenges faced in creating software to distill online collaboration into useful expertise. Explains how law, policy, and technology can be revamped to help government work in more open, participatory ways"--Provided by publisher